Relationships between symptom control, medication management, and health literacy of patients with asthma in Vietnam - Doan Thi Kim Cuc; Nonglak Methakanjanasak; Ho Thi Thuy Trang (Belitung Raya Foundation, Indonesia, 2021)
Background: Asthma is a significant health issue among Vietnamese adults in both urban and rural areas. The disease needs serious concern to minimize impact and improve the situation. Objective: This study aimed to describe the level of health literacy, symptom control, and medication management and determine the relationships among them in patients with asthma in Da Nang, Vietnam. Methods: A cross-sectional descriptive study was conducted among 84 patients with asthma. The questionnaires were used in this study, including demographic form, the Short-Form Health Literacy questionnaire (HL-SF12), Asthma Control Test (ACT), and Medication Adherence Reporting Scale for Asthma (MARS-A). Pearson product-moment correlation was applied to determine the relationship between health literacy, symptom control, and medication management. Results: The score revealed for general-health literacy, symptom control, and medication management were 28.70 (SD = 9.66), 17.72 (SD = 4.67), and 3.63 (SD = 0.75), respectively. Health literacy level had moderate positive relationships with symptom control (r = 0.41) and medication management (r = 0.44). Conclusion: The patients had limited health literacy, partially controlled symptom, and poor adherence to the medication. Health literacy level had moderate positive relationships with symptom control and medication management. These findings are crucial for effective treatment and management of the disease in Vietnam. To improve medication management and symptom control among patients with asthma, nurses should concern patients’ health literacy level.